Communication Anxiety and Speaking Performance in EFL Learners: A Systematic Review of Counseling and Pedagogical Strategies - Nur Cahya; Elfi Churnia (Indonesian Journal of Educational Counseling, 2026)
Communication anxiety is a persistent affective barrier that significantly hinders English as a Foreign Language (EFL) learners’ speaking performance. This systematic review synthesizes empirical studies published in the past five years to identify key psychological, linguistic, and instructional factors contributing to communication anxiety and to evaluate counseling-based and pedagogical interventions. Guided by PRISMA 2020 procedures, a comprehensive search across Scopus, Web of Science, ERIC, ScienceDirect, DOAJ, and Google Scholar identified 82 eligible studies. Findings indicate that communication anxiety is closely linked to fear of negative evaluation, linguistic insecurity, and low communicative self-efficacy. Teacher-centered instruction, strict error correction, and competitive classroom environments amplify anxiety, whereas supportive pedagogical climates increase learners’ willingness to communicate. Anxiety was consistently shown to disrupt fluency, lexical access, coherence, and spontaneous speech production. Counseling-based interventions including cognitive restructuring, mindfulness, relaxation training, and individual counseling effectively reduced affective symptoms and improved emotional regulation. Pedagogical strategies such as peer interaction, task repetition, scaffolded speaking tasks, and technology-mediated practice also contributed to reduced anxiety and improved oral performance. Integrated approaches that combine psychological and instructional support produced the most stable gains. Overall, the review emphasizes the importance of holistic teaching frameworks that simultaneously address affective needs and communicative competence, offering theoretical and practical insights for designing anxiety-sensitive speaking instruction in EFL contexts.